A detailed study of 4g in wireless communication : looking insight in issues in ofdm - Dewangan, Neelam (Anchor Academic Publishing, 2014)
As a promising technique, OFDM has been widely used in emerging broadband communication systems, such as digital audio broadcasting (DAB), high-definition television (HDTV), and wireless local area network (IEEE 802.11a and HIPERLAN/2). However, as the OFDM signals are the sum of signals with random amplitude and phase, they are likely to have large PAPR that require a linear high-power- amplifier (HPA) with an extremely high dynamic range which is expensive and inefficient. Furthermore, any amplifier nonlinearity causes intermodulation products resulting in unwanted out-of-band power.